Roles for jasmonate- and ethylene-induced transcription factors in the ability of Arabidopsis to respond differentially to damage caused by two insect herbivores - Rehrig, Erin M.; Appel, Heidi M.; Jones, A. Daniel; Schultz, Jack C. (Frontiers in Plant Science, 2014)
Plant responses to insects and wounding involve substantial transcriptional reprogramming that integrates hormonal, metabolic, and physiological events. The ability to respond differentially to various stresses, including wounding, generally involves hormone signaling and trans-acting regulatory factors. Evidence of the importance of transcription factors (TFs) in responses to insects is also accumulating. However, the relationships among hormone signaling, TF activity, and ability to respond specifically to different insects are uncertain. We examined transcriptional and hormonal changes in Arabidopsis thaliana after herbivory by larvae of two lepidopteran species, Spodoptera exigua (Hübner) and Pieris rapae L. over a 24-hour time course. Transcriptional responses to the two insects differed and were frequently weaker or absent in response to the specialist P. rapae. Using microarray analysis and qRT-PCR, we found 141 transcription factors, including many AP2/ERFs (Ethylene Response Factors) and selected defense-related genes, to be differentially regulated in response to the two insect species or wounding. Jasmonic Acid (JA), JA-isoleucine, and ethylene production by Arabidopsis plants increased after attack by both insect species. However, the amounts and timing of ethylene production differed between the two herbivory treatments. Our results support the hypothesis that the different responses to these two insects involve modifications of JA-signaling events and activation of different subsets of ERF transcription factors, resulting in different degrees of divergence from responses to wounding alone.